2006
DOI: 10.1021/jf0529823
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Surface Treatments of Cork Stoppers by FTIR-ATR

Abstract: A general method is described for the identification of paraffin- and silicone-based surface treatments applied to single-piece natural and 1 + 1 (cork agglomerate with two natural cork disks) cork stoppers used to seal wine bottles. The method is based on Fourier transformed infrared spectroscopy (FTIR) and attenuated total reflectance (ATR) analysis of ready-for-use stoppers. The absorbance in seven wavelength bands selected as the most characteristic (2916 and 2850 cm(-)(1), for paraffins, and 2963, 1258, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…The noise level was set to 0.02. Absorbance numerical values were obtained from each spectrum for the predetermined wavelengths (Ortega-Fernandez et al 2006).…”
Section: Infrared Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The noise level was set to 0.02. Absorbance numerical values were obtained from each spectrum for the predetermined wavelengths (Ortega-Fernandez et al 2006).…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…A previous study (Ortega-Fernandez et al 2006) reported on the possibility of detecting the presence and the type of treatment applied to a stopper by using the attenuated total reflectance-fourier transform infrared (ATR-FTIR) technique. The same technique has been applied recently for the characterization of paper finishes and to determine polymeric film thickness from 10 to 110 nm (Yang et al 2005), thinner than that used to coat cork stoppers.…”
Section: Introductionmentioning
confidence: 99%
“…This striking difference might be related to the coating whereas the coating thickness is about 50 mm and may consist of silicone, paraffin, and other resin compounds. [4] Therefore, the proton beam is probing mostly the elements present in the substances used during the cork coating procedure, which may differ from bulk concentrations. Two elements appear to have a distinct behavior from those mentioned in the aforementioned text: P and Cl.…”
Section: Wine and Corkmentioning
confidence: 99%
“…Finally, the finishing process takes place when the stoppers are washed, bleached, and their surfaces are treated with resins, silicone, or paraffin compounds to improve their sealant properties. [4] At different stages of processing, it has been shown that cork has the ability to absorb or emit substances depending on time of interaction and temperature. [5,6] Independently of the nature of the stopper (cork, synthetic, or twist-off cap), in principle, it should not interfere with the quality of the wine.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the treatment of the stopper/ closure surface with paraffins and silicones is critical to improve the sealant properties and the removal from bottleneck. The lubrification treatment facilitates insertion into and extraction from the bottle of the closure/cork, by reducing friction (Ortega-Fernández et al, 2006).…”
Section: Mechanical Properties Of Closuresmentioning
confidence: 99%